Clinically meaningful biomarkers for psychosis: A systematic and quantitative review - Prata, Diana; Mechelli, Andrea; Kapur, Shitij (Neuroscience and biobehavioral reviews, 2014)
Despite five decades of search for clinically meaningful 'biomarkers' in schizophrenia there are still no common tests to inform diagnosis or treatment. Our aim was to understand why it has been so difficult to convert biological findings into clinical tests. We categorized all PubMed-indexed articles investigating psychosis-related biomarkers to date (over 3200). Studies showed an evident publication bias, a confusing array of terminology, and few systematic efforts at longitudinal evaluation or external validation. Fewer than 200 studies investigated biomarkers, longitudinally, for prediction of illness course and treatment response. These biomarkers were then evaluated in terms of their statistical reliability and clinical effect size. Only one passed our a priori threshold for clinical applicability. This is a modest record. In order to promote real progress, the field needs: (a) consistent use of terminology so that studies can be compared; (b) a system of standardized universal reporting to overcome the existing publication bias; and (c) practical criteria [a prototype is suggested here] for assessing the clinical applicability of the findings.